Present stereotypes in the choice of academic careers and professional training - Ordóñez-Olmedo., Eva; Fernández-Pardavila, Mª. José; Mac-Fadden, Isotta (IJERI: International Journal of Educational Research and Innovation, 2020)
This paper analyzes how gender stereotypes influence differently the way men and women decide about their professional future. Quantitative research has been designed in order to know what are the beliefs and stereotypes that presently influence the process of decision making of the individual when choosing their academic career. The research is carried out from a double perspective, analyzing on the one hand the beliefs, motivations, and stereotypes of the students, and on the other hand, identifying in the Galician society the beliefs in relation to professional competence and the stereotypes that connect to each gender . These data will be correlated with the number of registered students in each of these degrees of each gender in order to identify what weight stereotypes exercise when deciding a profession.